Radiouitzendingen "De Roode Haan" en "Het Capitool" met interviews met Buijs en specialisten in ziekenhuizen
Radiouitzendingen "De Roode Haan" en "Het Capitool" met interviews met Buijs en specialisten in ziekenhuizen.